PENGARUH PROFITABILITAS, KEPEMILIKAN MANAJEMEN DAN MEDIA EXPOSURE PADA PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) - Ni Kadek Devi Juliantari; Sang Ayu Putu Arie Indraswarawati (UNHI Press, 2020)
This study aims to find out the effect of profitability, management ownership, and mediai exposurei on corporatei social responsibilityi disclosure. This study uses manufacturing companies listed on the Indonesiai Stock Exchange (IDX) in 2015- 2017 as population and sample. The number of research population is 140 manufacturing companies. In order to get the right sample, the researchers used a purposive sampling method and selected 45 companies that met the criteria. The analysis technique used in this study is multiple linear regression analysis techniques. Based on the results of analysis shows that profitability affects CSRi. While manageent ownership has on effect on CSRi, and mediai exposurei variables have no effect on CSRi.